Electromagnetic noise-immunity improving of signal transducers based on Hall sensors - Hotra, Z. Yu.; Holyaka, R. L.; Ilkanych, V. Yu.; Marusenkova, T. A.; Boyko, O. V. (Technology and design in electronic equipment, 2013)
The authors consider electromagnetic noise cancellation in galvano¬magnetic magnetic field measurement devices based on Hall sensors. The paper presents the advanced microprocessor signal transducer featuring high noise-immunity, provided by two-stage signal measurement at reversed directions of Hall sensor supply current. It is shown that the use of two-stage mode at high electromagnetic interference provides the improvement of signal measurement results reproducibility up to 8 times.